1951
DOI: 10.1002/aja.1000880204
|View full text |Cite
|
Sign up to set email alerts
|

The comparative anatomy of the hypophysis, with special reference to its blood supply and innervation

Abstract: This paper is primarily concerned with the coniparative anatoiiiy of pituitary vessels and nerves. Other aspects of the histology aiid cytology of the gland will also be considered, especially in those species which have received little attention. Except in the niammals, little is known about hypophyseal vessels arid accounts of the innervation of the hypophysis a r e inadequate arid contradictory.Shorter investigatioiis of these structures in some common laboratory mammals (Green and IIarris, '46, '47) , in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1

Year Published

1954
1954
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(66 citation statements)
references
References 109 publications
3
62
1
Order By: Relevance
“…; Xuereb et al, 1954aXuereb et al, , 1954bGreen, 1957;Stanfield, i960), in the monkey (Wislocki and King, 1936;Wislocki, 1938aWislocki, , 1938bHolmes and Zuckerman, 1959), in the sheep Prichard, 1957a, 1957b;Baldwin, 1964), in the goat (Daniel and Prichard, 1958;Adams £t 1964b), in the horse (Baldwin, 1964;BrettSchneider, 1955), in cattle (Baldwin and Bell, 196O; Dellmann, I960; Baldwin, 1964;Cummings and Habel, 1966), in the cat (Wislocki and King, 1936;Wislocki, 1937c;Green and Harris, 1947; Torok, 196O; Szentagothai e^^., I968), in the rabbit (Wislocki and King, 1936;Harris, 1947), in the rat (Green and Harris, (Green, 1951;Daniel, 1966). In species where the internal carotid artery remained patent in the adult animals, it was estab lished that the rostral hypophysial arteries took their origin from the intra-arachnoid portion of the internal carotid or from the caudal communicating artery (Basir, 1932;Torok, 1964;Stanfield, 196O).…”
Section: Omentioning
confidence: 99%
See 2 more Smart Citations
“…; Xuereb et al, 1954aXuereb et al, , 1954bGreen, 1957;Stanfield, i960), in the monkey (Wislocki and King, 1936;Wislocki, 1938aWislocki, , 1938bHolmes and Zuckerman, 1959), in the sheep Prichard, 1957a, 1957b;Baldwin, 1964), in the goat (Daniel and Prichard, 1958;Adams £t 1964b), in the horse (Baldwin, 1964;BrettSchneider, 1955), in cattle (Baldwin and Bell, 196O; Dellmann, I960; Baldwin, 1964;Cummings and Habel, 1966), in the cat (Wislocki and King, 1936;Wislocki, 1937c;Green and Harris, 1947; Torok, 196O; Szentagothai e^^., I968), in the rabbit (Wislocki and King, 1936;Harris, 1947), in the rat (Green and Harris, (Green, 1951;Daniel, 1966). In species where the internal carotid artery remained patent in the adult animals, it was estab lished that the rostral hypophysial arteries took their origin from the intra-arachnoid portion of the internal carotid or from the caudal communicating artery (Basir, 1932;Torok, 1964;Stanfield, 196O).…”
Section: Omentioning
confidence: 99%
“…The vascularity of the Junctional zone with the pars intermedia is especially prominent (Christ, 1966;Gabe, 1966). In many species, the two lobes have a common vascular supply (Green, 1951).…”
Section: The Pars Distalis Neurohypophysis Has a Rich Vascularmentioning
confidence: 99%
See 1 more Smart Citation
“…Light microscope methods have also long shown that in man and various animals, including the rat, the primary capillary plexus of the hypophyseal portal system has many communications with the hypothalamic vessels (for reference, see : DANIEL, 1966;GREEN, 1966;WINGSTRAND, 1966;BERGLAND and PAGE, 1979). However, these communications have been a subject of controversy.…”
mentioning
confidence: 99%
“…The conventional light microscope method has long established that in man and various animals, including the rat that the hypophyseal portal system originates in the primary capillary plexus in the median eminence, infundibulum and stalk, and terminates in the secondary capillary plexus in the pars distalis (for references, see : DANIEL, 1966;CHRIST, 1966;GREEN, 1966;WINGSTRAND, 1966;BERGLAND and PAGE, 1979). Scanning observation of the vascular casts has clearly comfirmed in the monkey, dog, rat and some other animals this, or long portal system, as well as the so-called short portal system connecting the infundibular process and pars distalis (MURAKAMI, 1975a, b ;PAGE et al, 1976PAGE et al, , 1978PAGE and BERGLAND, 1977;LAMETSCHWANDTNER et al, 1977;PAGE, 1978, 1979;OHTANI et al, 1983;KIKUTA et al, 1984;MURAKAMI et al,' 1985).…”
mentioning
confidence: 99%